Experimental investigation of the effect of urea addition to fuel on engine performance and emissions in diesel engines - Demir, U.; Kozan, A.; Özer, Salih (Elsevier Ltd, 2022)
Today, exhaust emissions have become a critical issue with the increasing number of vehicles due to greenhouse gas. Engine manufacturers carry out R&D studies due to emission limitations imposed on engines that use fossil fuels. Selective Catalytic Reactor and AdBlue injection systems have been used significantly to reduce NOx emissions in diesel engines. For this reason, AdBlue is sprayed in the exhaust manifold to reduce emissions with a second injector in diesel engines. In this study, the effects of commercial AdBlue, Urea-pure water mixture and urea- pure water-citric acid mixtures as additives to diesel fuel on exhaust emission and performance in a diesel single-cylinder engine were investigated. In-cylinder pressure, exhaust gas temperature, fuel consumption, air consumption and exhaust emissions were measured experimentally to examine the effects of 3 different mixtures added to diesel fuel at 8 different loads. As a result, urea-citric acid–water mixtures added to diesel fuel worsened combustion. Brake fuel specific consumption has increased 8% for diesel + urea + citric acid mixtures due to the presence of water in mixtures. CO2 emissions increased by 38% with the addition of AdBlue, while an increase of 53% was observed with the addition of diesel + urea + citric acid. With the addition of urea + citric acid to diesel fuel, CO emissions decreased by 233%, while under the same conditions, HC emissions decreased by 300% and NOx emissions decreased by a maximum of 19%. © 2021 Elsevier Ltd
Keywords: Addition Urea, AdBlue and Citric Acid to Diesel Fuel; Diesel Engine; Engine Performance; Exhaust Emission; Additives; Automobile manufacture; Citric acid; Diesel engines; Diesel fuels; Exhaust gases; Fossil fuels; Gas emissions; Greenhouse gases; Metabolism; Mixtures; Nitrogen oxides; Acid mixtures; Addition urea, adblue and citric acid to diesel fuel; Critical issues; Engine emission; Engine performance; Exhausts emissions; Experimental investigations; Number of vehicles; Performance and emissions; Pure water; Urea